2023
DOI: 10.3390/nano13020360
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials for Catalysis and Energy Storage

Abstract: The development of nanomaterials with different shapes and sizes and which are utilized as effective materials for energy and environmental applications constitutes a challenge for researchers [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…The small white particles observed on the surface of the coated tool are associated with the presence of the TiN compound. [9,10] In Figure 2b, it can be observed that there are white droplets and pits on the surface of the TiN coating. This is due to the intrinsic characteristics of the deposition technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small white particles observed on the surface of the coated tool are associated with the presence of the TiN compound. [9,10] In Figure 2b, it can be observed that there are white droplets and pits on the surface of the TiN coating. This is due to the intrinsic characteristics of the deposition technique.…”
Section: Resultsmentioning
confidence: 99%
“…The small white particles observed on the surface of the coated tool are associated with the presence of the TiN compound. [ 9,10 ]…”
Section: Resultsmentioning
confidence: 99%
“…The energy crisis is, with the massive consumption of fossil fuels, one of the major issues in modern society. , Therefore, energy storage must be demanded, which could reduce the gap between its utilization and turnout. Supercapacitors are a kind of clean and sustainable energy storage devices that have become a hot topic due to their high power density, fast charge–discharge cycles, eco-friendliness, wide operating range, and long cycle life. Supercapacitors have been investigated for different energy storage applications, such as larger-scale electrical lines, transportation (electric buses, trucks, and heavy-duty vehicles), power supply backup, memory backup, portable devices (phones, digital cameras, and laptops), wearable electronic devices, smart grids, satellite applications, and military applications. Therefore, they play an important role in people’s daily life. , They can store energy in two ways: (i) oxidation–reduction (redox) reactions between the electrolyte and electrode (pseudocapacitors) and (ii) ion adsorption on the electrode (electrochemical double-layer capacitors). , …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the advancement in nanoscience and nanotechnology has attained the impressive attention of many scientists owing to the significant impact of these technologies on the growth in this modern era of science. These technologies have a wide range of commercial applications in food industries [1], pharmaceutical industries [2], chemical industries [3], energy conversion and storage devices [4][5][6], and many other domains of life, in addition to toxic chemical sensing in our ecosystem [7][8][9]. Their advancement relies on the production of semiconductor nanostructure materials of different kinds of metal oxides, along with their unique morphologies at nano scales.…”
Section: Introductionmentioning
confidence: 99%